A case study of third grade students' perceptions of the station rotation blended learning model in the United States. Issue 2 (3rd April 2018) - Truitt, Apricot A.; Ku, Heng-Yu
ABSTRACT: The purpose of this case study was to explore the experiences of 31 third graders who experienced learning in a Station Rotation blended learning setting over the period of one semester in the United State. These students participated in student focus group interviews and completed student questionnaires during the middle and the end of the semester. The student focus group interviews were first transcribed and coded. The students' responses from the questionnaires were then coded and compared with the findings from the student focus group interviews. The results revealed five positive themes (variety of activities, technology, learning, fun, and getting help) and two negative themes (challenging work and technology). These emerged themes from the student focus interviews and the student questionnaires explain the perceptions the students had about the Station Rotation blended learning model. Finally, discussion for current study as well as recommendations for future research were provided.